Ethical of Using Artificial Intelligence in Learning: Perception of College Students in the Islamic Education Study Program - Uun Kurnaesih; Faizudin; Sayuti; Ahmad Munji; Ade Imun Romadan (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Artificial intelligence (AI) is a key component of digital literacy systems. AI is a major innovation in the field of education that has the potential to significantly improve learning, and also educational administration. Based on observations made at STIT Al-Khairiyah Cilegon, Banten, this research intends to explore the morality of using AI in the classroom as perceived by college students enrolled in Islamic education programs. Phenomenological techniques combined with descriptive qualitative research are employed to address predetermined goals. The methods of interviewing, and the Miles, Huberman, and Saldaña models for data analysis, data condensation, data display, and conclusion drawing are all used in data collection. Based on the study findings and also discussions, AI-based technology makes tasks more efficient and helps students comprehend their study materials more fully. College students with strong religious backgrounds exhibit a more critical attitude toward the use of AI, putting forth high ethical considerations to ensure that the use of AI always stays in line with Islamic principles with a combination of structured academic training and religious feeding. The ethich of using AI in learning are focused on three things, namely data privacy-security, plagiarism avoidance, and responsibility. This study offers a theoretical addition and offers insightful information about the role of AI in Islamic education.